2010
DOI: 10.4103/0022-3859.65279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of primary hyperparathyroidism from western India

Abstract: PHPT in western India is symptomatic disorder with skeletal and renal manifestations at a much younger age. Clinical profile of PHPT in children is similar to that of adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 16 publications
7
50
3
2
Order By: Relevance
“…Recent case series from Asia reported much higher prevalence rates of 24-87% (31,32,33,34), whereas a case series from Saudi Arabia documented a prevalence rate of only 4% (35).…”
Section: Prevalence Of Hbs After Parathyroidectomymentioning
confidence: 99%
“…Recent case series from Asia reported much higher prevalence rates of 24-87% (31,32,33,34), whereas a case series from Saudi Arabia documented a prevalence rate of only 4% (35).…”
Section: Prevalence Of Hbs After Parathyroidectomymentioning
confidence: 99%
“…In a study of 39 patients of PHPT by Priya et al , 78% of the patients had neuromuscular weakness and 28% had concomitant vitamin D deficiency 3. Similarly in a recent single centre study of 79 patients by Gopal et al , the prevalence of neuromuscular weakness was 45.5% 4. The same trend was shown in a recent review of multi-centre data 5.…”
Section: Discussionmentioning
confidence: 69%
“…In a systematic review on PHPT, in India, reported by various tertiary care institutes (344 PHPT cases) across the country showed the rate of renal disease in 36% cases (9). Gopal et al reported renal calculi including nephrocalcinosis in 40.5% of the PHPT patients (10). Renal stone disease was present in 78% cases of symptomatic and in 35.5% asymptomatic PHPT patients has reported in another study by Cipriani et al (11).…”
Section: Discussionmentioning
confidence: 93%